DETERMINANTS OF PSYCHOSOCIAL REACTIONS IN UNIVERSITY STUDENTS POST COVID-19: A CROSS-SECTIONAL STUDY - Ghafoor, Muqqadas; Khan Lodhi, Mishal (Journal of Pakistan Psychiatric Society, 2023)
Objective: To identify the mediating role of Perceived Social Support in Psychological Strength and Psychosocial Reactions in university students post COVID-19. Study Design: Cross-sectional (correlation) research design was used. Place and Duration of study: The data was collected from November 2021 to January 2022 from different state and private universities in Lahore, Pakistan. Subject and Method: The purposive sample of N=150 (men=70 and women=80) university students studying in first and last year of 18-24 years old (M=20.75, SD=1.76) were drawn from different public and private universities of Lahore. Data was collected using Psychological Strength Scale (PSS; Bashir, 2020), Multidimensional Scale of Perceived Social Support (MSPSS; Zimet et al., 19 88) and Psychosocial Reactions Scale (PRS; Mahmood et al., 2020). Data was analyzed using SPSS 25. Results: Of the 150 participants, 70(46.7%) were men and 80(53.3%) were women. The overall mean age was 20.75 ± 1.76 years. Pearson Product Moment Correlation revealed that a significant negative relation of Psychological Strength and Perceived Social Support with Psychosocial Reactions. Psychological Strength and Perceived Social Support had positive significant relationship (r= .68***), but a negative relationship between Perceived Social Support and Psychosocial Reactions (r= -.56***) and Psychological Strength with Psychosocial Reactions (r= -.33***) was also found in university students post COVID-19. Mediation analysis showed that Perceived Social Support fully mediated the relation among Psychological Strength and Psychosocial Reactions (p<.001). Conclusion: Study implicates that by increasing Psychological Strength and Perceived Social Support in university students we could reduce Psychosocial Reactions faced by them.